2010
DOI: 10.7146/tfss.v7i13.4149
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped perceptions of chronic pain

Abstract: This essay is a reflection on my professional norms when I do pain research, treat pain patients, and communicate with the social system. Being both a medical doctorand a clinical researcher, I daily have to combine what I see as arbitrary rationalities in my approach to pain. The reason is that pain research is often conducted within a theoretical framework that mainly understands pain as a physical or biomedical phenomenon even though a broader and more precise perspective on pain exists - and is often used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Furthermore, our study does not say anything about GPs' actual discretionary practices, pointing towards the relevance of further exploration on GP-patient encounters, including patients' experiences so as to shed light on patients' demands and their expectations to GPs' handling of preventive consultations. Even though no empirical generalizations can be made, our analysis support findings from earlier studies on SLBs' discretionary practices, suggesting that other sources than formal rules inform the discretion at the frontline (Dubois, 2010;Møller, 2011;Maynard-Moody & Musheno, 2003;Harrits & Møller, 2014;Watkins-Hayes, 2011). Furthermore, GPs comprise a case of a professional social group (Freidson, 1970(Freidson, /2007)-the medical professionmeaning that if their discretionary practices are influenced by their own lifestyle, we think it is reasonable to assume that this might also be the case of other in other professional social groups, such as among pedagogues and teachers, who are also in close contact with citizens and with the task of implementing preventive policies.…”
Section: Concluding Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, our study does not say anything about GPs' actual discretionary practices, pointing towards the relevance of further exploration on GP-patient encounters, including patients' experiences so as to shed light on patients' demands and their expectations to GPs' handling of preventive consultations. Even though no empirical generalizations can be made, our analysis support findings from earlier studies on SLBs' discretionary practices, suggesting that other sources than formal rules inform the discretion at the frontline (Dubois, 2010;Møller, 2011;Maynard-Moody & Musheno, 2003;Harrits & Møller, 2014;Watkins-Hayes, 2011). Furthermore, GPs comprise a case of a professional social group (Freidson, 1970(Freidson, /2007)-the medical professionmeaning that if their discretionary practices are influenced by their own lifestyle, we think it is reasonable to assume that this might also be the case of other in other professional social groups, such as among pedagogues and teachers, who are also in close contact with citizens and with the task of implementing preventive policies.…”
Section: Concluding Discussionsupporting
confidence: 79%
“…Years of research has demonstrated how different social mechanisms affect policy outcomes, when policy goals are ambiguous (Brodkin 2011, Maynard-Moody & Portillo, 2010. Other studies point to the fact that SLBs' discretion is influenced by much more than a regulative and a professional framework such as social stereotypes, social distance, personal values and moral concerns (Møller, 2011;Maynard-Moody & Musheno, 2003;Harrits & Møller, 2014;Watkins-Hayes, 2011) and how doctors' discretionary practices in medical encounters are also shaped by social background, ethnicity and gender (Bertakis, 2009;Sandhu, Adams, Singleton, Clark-Carter, & Kidd, 2009;van Ryn & Burke, 2000;Willems, De Maesschalck, Deveugele, Derese & De Maeseneer, 2005). However, despite the potential influence of these patient-factors on doctors' discretion it remains unclear how discretion is influenced by their own background and lifestyle as we prefer to address it here.…”
mentioning
confidence: 99%